Case Study and Hands On with the New DSL2 Electronic Initiation System - J. M. Laboz; Thierry Bernard (International Society of Explosives Engineers, 2000)
2000 HIGH-TECH SEMINAR Blasting Technology, Instrumentation and Explosives Applications